Beyond BCI—Validating a wireless, consumer-grade EEG headset against a medical-grade system for evaluating EEG effects of a test anxiety intervention in school. (August 2020) - Khng, Kiat Hui; Mane, Ravikiran
Abstract: Educational neuroscience is an emerging interdisciplinary field. However, the use of neuroimaging techniques and tools such as electroencephalography (EEG) in school-based interventions and research is limited, largely due to the high costs and physical constraints of conventional research- or medical-grade equipment. Neuroimaging and electrophysiological data can provide useful evidence to validate the efficacy of interventions. The present study explores the utility of lightweight, affordable, and easy-to-set-up EEG systems for use in school-based research with children. Specifically, we examine the effects of a deep-breathing-for-test-anxiety intervention on brain electrical activity during a flanker distractor interference task in eleven-year olds, comparing the pattern of results observed using a consumer-grade EEG system (Emotiv EPOC+) against that obtained using a medical-grade EEG system (Neurostyle). Behavioral, EEG, and respiratory data was obtained from Primary 5 students ( N  = 45; Mage  = 10.88, SD  = 0.33), split into Emotiv and Neurostyle groups. The aim of the study was two-fold: to examine the effects of deep breathing on neurophysiological and behavioral correlates of inhibitory control of attention in children, and to understand the affordances and limitations of the Emotiv EPOC+ system for school-based research with children. Results from power spectral analyses suggest that deep breathing may enhance attentional control on a neural level by modulating brain electrical activity on several frequencies. Despite limitations, the consumer-grade EEG system appears to be capable of detecting some degree of power spectral differences associated with intervention effects.